The Antibacterial Activity Of Crude Leaf Extract Of Citrus Sinensis (Sweet Orange) - Uchechi N. Ekwenye; Oghenerobo V. Edeha (International Journal of Pharma and Bio Sciences, 2010)
The antibacterial activity of Citrus sinensis was evaluated on bacteria strains like Escherichia coli, Pseudomonas aeruginosa , Klebsiella pneumoniae, and Staphylococcus aureus. Water and ethanol were used for the extraction. The in vitro antibacterial activity was performed by agar disc diffusion method. The antibacterial effect of aqueous extract showed a zone of inhibition on Escherichia coli, which was seven millimeter in diameter, while on the other organisms it showed little or no zones of inhibition ranging from 0-3mm in diameter. The ethanol extract also showed little zones of inhibition on the test organisms ranging from 1-3mm in diameter. The minimum inhibitory concentration (MIC) evaluated on the ethanol and aqueous extracts using a two fold serial dilution showed no zones of inhibition .The results obtained in this study suggested that the extracts have low potential for use in the treatment of diseases caused by these test organisms.